Responsible retrospection: adapting responsible innovation to the liminal innovation of ICTs - Ivan Veul; Lotte Krabbenborg (Journal of Responsible Innovation)
ICTs are ubiquitous in today's digitised societies, but Responsible Innovation (RI) approaches are ill-equipped to address the liminal nature of ICT innovation. ICTs remain malleable after their diffusion. As a result, they are often in use and in development at the same time. This liminality has allowed developers to innovate by updating established ICTs and to incorporate information about the use of ICTs into their innovation. This clashes with RI approaches, which focus on emerging technologies and anticipation. We suggest three adaptations to overcome the gap between RI's anticipatory approach and the liminal innovation of ICTs: (1) RI must broaden its scope to include both emerging and established ICTs. (2) RI must focus on how developers monitor their in-use ICTs, as this information greatly influences innovation. And (3) RI must reflect on how to retrospectively care for issues with in-use ICTs, now that it is possible to update in-use ICTs.